Determinants of Girls’ Educational Performances in Science, Technology, Engineering, and Mathematics (STEM) Subjects across Selected Schools in Oromia Regional State, Ethiopia - Kufi, Endalew Fufa (International Journal of STEM Education for Sustainability, 2023)
The purpose of this research was to investigate key determinants of girl’s performances in STEM subjects in selected schools of Oromia Regional State, Ethiopia. Interpretive explication method   was employed in which   interview and focus-group discussion were instruments of data collection. Participants’ interview and focus-group data were carefully collected based on which due transcription was made. In the transcription process, careful selection was made on issues that related to basic research questions. Then, coded categories were formed under each team to analyze the data.  The findings indicated   that, while girls outsmarted boys in almost all natural science and mathematics subjects, there were gaps among female students themselves owing to low economic standards to cover the costs of living and learning, negative peer-pressure, and shortage in schools to scale up intra-group support among female students. In spite of the existence of some outsmarting girls in schools who were able to perform much more than males, there also existed socio-economic determinants which created barriers on average achieving girls’ performances. There were also digital divides among girls from providing and less-providing homes from the point of view of facilities.